Creating Creative Industry Through Patches Using Sospeso Techniques - Sri Suryani Yuprapti Winasih; Wiwik Handayani; Zumrotul Fitriyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to provide skills and creative ideas to the community in Rejosari RW 03, Benowo Village, Pakal District, Surabaya, by utilizing patchwork waste into items of economic value so that it is expected to be able to produce home industry that can increase family income. This community service activity used the Participatory Action Research (PAR) method. Through the sospeso technique, the remnants of cloth that should be thrown away could be processed into handicrafts that have economic value and become potential for creative industries. The evaluation was carried out during the training process through the involvement and abilities of the participants while post-training through the level of completion of the material that was evaluated by observing and examining the work as well as giving a question-and-answer questionnaire. The results of this service activity provided creative ideas to housewives of Rejosari RW 03 by utilizing patchwork waste into sospeso products that decorated and beautified the appearance of bags, wallets, sandals, and other household items. The brooch could improve the skills of housewives, increase family income and maintain a clean environment, and increase value (product selling value).